Effect of Heat Treatment Process on the Section Shrinkage of 1Cr16Ni2MoN Blade Steel - Zhang Xiuli, Gong Zhihua, Liu Xinquan, Sun Guoyang, Ma Yuanyuan, Gao Xiang (Teshugang)
In order to solve the problem of unstable cross-sectional shrinkage of 1Cr16Ni2MoN steel， OIM， SEM， TEM， and thermodynamic calculations and other means were used to study the microstructure and ductility of 1Cr16Ni2MoN martensitic heat-resistant steel for gas turbine blades under different tempering processes. The results show that 1Cr16Ni2MoN steel quenched at 1 040 ℃ and 550 ℃-560 ℃， with a tensile strength of over 1 200 MPa， a yield strength of over 1 000 MPa， and a cross-sectional shrinkage rate of over 65%； The main type of carbide precipitation is M23C6， which forms a banded structure composed of large carbide particles due to Cr segregation in the microstructure， accompanied by the formation of δ-ferrite. With the increase of tempering temperature， the amount of carbide precipitation increases， and the carbide at grain boundary and Flat noodles boundary gathers and coarsens， which leads to the decrease of the bonding force between flat noodles and phase interface， which can accelerate the generation and propagation of cracks， thus reducing the reduction of area and impact toughness.Taking into account the control of δ - ferrite and cross-sectional shrinkage rate， it is necessary to adjust the composition， the content of C should be minimized as much as possible， with the carbon content maintained at 0.15%， the content of N should be suitably increased to upper limit of 0.007%， and the diffusion annealing process should be implemented to reduce the enrichment of carbides resulting from segregation.